In vitro H1-receptor antagonist activity of methanolic extract of tuber of Stephania glabra - Khan, Nisar Ahmad; Kumar, Dinesh; Bhat, Zulfiqar Ali; Kumar, Vijender; Nagpal, Navneet; Bhujbal, Santosh S. (Bangladesh Journal of Pharmacology, 2011)
In the present study, methanolic extract of tuber of Stephania glabra was evaluated for H1-bloker activity by employing in vitro screening models of guinea pig ileum and goat tracheal chain preparation. Goat isolated trachea and guinea pig ileum contracted to histamine in a dose-dependent manner while chlorpheniramine blocked this effect. The methanolic extract produced significant dose-dependent H1-receptor antagonist activity by blocking histamine-induced contraction.